Do Neighbors Affect People's Demand for the Biodiversity Conservation Project in the U Minh Ha Peat Swamp Forest of the Mekong Delta, Vietnam? - Khai, Huynh Viet; Utsunomiya, Yuzuru; Khong, Tien Dung; Khoi, Le Nguyen Doan (Frontiers in Sustainable Food Systems, 2022)
Despite incentives and measures taken to improve forest conservation, deforestation in Vietnam continues to increase. Seeking community participation in this activity is considered one of the most effective measures in developing countries. This research, therefore, applies the contingent valuation method (CVM) approach to estimate the residents' demand or willingness to pay for the U Minh Ha forest conservation project in Vietnam. The results indicated that respondents were willing to contribute about 4.3 kg of rice per month to the project. The results also indicated that respondents who knew neighbors' participation in the conservation project and thought that forest ecotourism had benefits for their families were more likely to contribute to the conservation project. We then conclude that forest sustainability in developing countries significantly depends on the community's preferences and is robust by neighbor participation.